Donor-acceptor anchoring nanoarchitectonics in polymeric carbon nitride for rapid charge transfer and enhanced visible-light photocatalytic hydrogen evolution reaction. (September 2022) - Liu, Runlu; Liu, Siyuan; Lin, Jingyi; Li, Yao; Chen, Shunwei; Wang, Peikui; Zhu, Shenmin; Han, Xiujun; Wang, John
Abstract: Polymeric carbon nitride (PCN) is a promising candidate for photocatalytic hydrogen evolution reaction (HER). However, the fast recombination of photogenerated charge carriers often gives an overall poor photocatalytic activity. Herein, we report anchoring of a donor-acceptor structure into the C–N skeleton, made in one-pot synthesis, where thiophene and cyano groups are introduced as the donor and acceptor, respectively, to modulate the electronic structure of pristine PCN. The separation and migration of the photogenerated charge-carriers in the PCN with donor-acceptor structure (CN-Cy-Th) were significantly promoted due to the enlarged π-conjugated system and much strengthened electron-redistribution effect, as confirmed by a series of experimental characterizations and density functional theory calculations. As such, the CN-Cy-Th exhibited a remarkable visible-light photocatalytic hydrogen evolution rate of 2.448 mmol g −1 h −1, which was 9.0-fold rise as compared with that of pristine PCN (Bulk CN). This work provides a facile and effective new pathway for accelerating the transfer of photogenerated charge carriers in semiconducting materials and constructing high performance photocatalysts. Graphical abstract: To solve the problem of fast recombination of photogenerated charge carriers and poor photocatalytic activity of pristine polymeric carbon nitride (PCN), we anchored a donor-acceptor structure into the C–N skeleton, where thiophene and cyano groups were introduced as the donor and acceptor, respectively, to modulate the electronic structure of pristine PCN. The separation and migration of the photogenerated charge-carriers in the PCN with donor-acceptor structure (CN-Cy-Th) were significantly promoted due to the enlarged π-conjugated system and much strengthened electron-redistribution effect, as confirmed by a series of experimental characterizations and density functional theory calculations. As such, the CN-Cy-Th exhibited a remarkable visible-light photocatalytic hydrogen evolution rate of 2.448 mmol g −1 h −1, which was 9.0-fold rise as compared with that of pristine PCN (Bulk CN). This work provides a facile and effective new pathway for accelerating the transfer of photogenerated charge carriers in semiconducting materials and constructing high performance photocatalysts. Image 1